Orbital-scale variations in mineral composition and organic-matter enrichment in the lower Cambrian Qiongzhusi formation shale, Deyang–Anyue Rift Trough, Sichuan Basin, China - Xuan’ang Zhang; Jianping Yan; Xiaoxue Qiu; Maojie Liao; Xuewen Shi; Shaolong Zhang; Wei Guo; Majia Zheng; Jingong Cai (Journal of Asian Earth Sciences, 2026)

Imbalance-aware spectral classification via logit-label adjustment and multi-expert mutual learning - Wei Luo; Haiming Yao; Tao Zhou; Ang Gao; Shilong Yang; Xue Wang (Analytica Chimica Acta, 2026)

Occurrence and behaviors of organophosphate esters in shallow grass-type lake ecosystems: The key role of aquatic plants - Mei Wang; Bing Wang; Yifan Zhang; Yihang Sun; Jingjing Zhao; Ang Zhao; Chao Wei (Water Research, 2026)

Mussel-inspired construction of superhydrophilic/underwater superoleophobic PTFE membranes using a novel ε-polylysine-based modification for efficient oil-water separation - Xin Wu; Chenyang Li; Shuiling Hong; Ang Gao; Haoming Duan; Wei Li; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Development of a global integrated environmental quality index for population health research - Wenjie Ruan; Qi Zhao; Xiaoyue Liu; Lina Ang; Haitong Zhe Sun; Wei Jie Seow (Environmental Pollution, 2026)

Elucidating the effect of reactor configuration on xylan recovery during reductive alkaline hydrogen peroxide pretreatment system with implications for scale-up - Nur Syahirah Ahmad Sobri; Shuhaida Harun; Wei Feng Ang; Peer Mohamed Abdul; Muhammad Zulhaziman Mat Salleh (Chemical Engineering Journal, 2026)

Identification, characterization and biogenic fungicide screening of Macrophomina phaseolina (Tassi) Goid. causing root rot in Atractylodes lancea (Thunb.) DC. - Haonan Shen; Ruixin Ju; Ang Li; Min Tang; Xiaomeng Fei; Yueyu Ye; Lixia Wang; Fang Tian; Wei Gu (Australasian Plant Pathology, 2026)

Zinc co-exposure with different antibiotic classes drives distinct microbial community restructuring in activated sludge - Yu Ang Li; Shijie Dong; Yongchao Li; Wei Wen; Mengbo Yuan; Jiangxiao Luo; Bin Shi; Renxin Zhao (Journal of Hazardous Materials, 2026)

Using machine learning models to estimate ecotoxicity effect factors for various nanomaterials in life cycle assessment - Xiao Li; Yuan Yuan; Ang Li; Wei Sun; Weichun Ma (Journal of Hazardous Materials, 2026)

Tissue-specific energy trade-off strategies in Mytilus coruscus under combined stress of nano-TiO2 and marine heatwaves - Bing Liu; Sijie Fan; Menghong Hu; Li'ang Li; Mojiang Zhang; Xinyue Li; Moslem Sharifinia; Piotr Maszczyk; Nisha Singh; Waiho Khor; Hanafiah Fazhan; Wei Liu; et al. (Aquatic Toxicology, 2026)

Predicting drug release from polymeric long-acting injectables using a machine learning approach to decode formulation-performance relationships - Tianqi Wang; Tianyu Liu; Xiaoying Xu; Joyce Wen Hui Ang; Somabha Mukherjee; Tina T. Wong; Jiong-Wei Wang; Matthias G. Wacker (Drug Delivery and Translational Research, 2026)

Designing hard-soft carbon composite anodes via a normalized pore volume-mass matching strategy for high-performance sodium storage - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Xiaofeng Zhang; Haiyan Liu; Chengwei Fan; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2026)

Organophosphate triesters and diesters in the Yellow River Basin (Shandong section): Geographical patterns, land use correlates and compound-specific source apportionment - Yuting Ren; Lin Zhu; Huijie Dang; Lili Cui; Ang Zhao; Chao Wei; Mei Wang (Marine Pollution Bulletin, 2026)

Microbial community shift and functional reorganization from influent to effluent in wastewater treatment plants on the Qinghai–Tibet Plateau - Yongchao Li; Bin Shi; Di Li; Yu-Ang Li; Mengbo Yuan; Jiangxiao Luo; Shijie Dong; Wei Wen; Renxin Zhao (Journal of Environmental Management, 2026)

A proof of concept study of electrocoagulation powered by an electro-wetland for hexavalent chromium removal from wastewater - Xiaorui Lei; Yaqian Zhao; Ting Wei; Yi Mao; Fuhao Zhang; Ang Liu; Yujie Yuan (Chemical Engineering Journal, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Which built environment factors promote urban residents' climate change adaptive behaviors? Multi-group application of an exploratory framework via adaptive motivations' mediation - Runsheng Jiang; Wei Dong; Lan Bai; Ang Qu; Yu Dong (Sustainable Cities and Society, 2026)

Exploring advanced measures of constructed wetland for the improved removal of emerging contaminants - Ang Liu; Yaqian Zhao; Jiwei Zhu; Ting Wei; Kaiyue Hao; Liu Yang; Carlos A. Arias; Juan A. Baeza (Journal of Environmental Management, 2026)

N-halamine-grafted MIL-125-NH2(Ti) as a long-lasting chlorine reservoir for round-the-clock decontamination of Aspergillus aerosols - Ruirui Hou; Hao Yang; Fengming Hou; Yihang Li; Zhipeng Guo; Jin Li; Wei Wei; Ang Wei (Chemical Engineering Journal, 2026)

Phenothiazine-based polymer anode enabling long-cycle aqueous rechargeable batteries under acidic and alkaline conditions - Yunpeng Zhou; Shibo An; Yongzhihan He; Huilin Wei; Jun Yang; Minjie Shi; Lintong Hu; Edison Huixiang Ang (Chemical Engineering Journal, 2026)

Contamination of commercial 15 N 2 : potential impacts on nitrogen fixation assays and a simple method for quantification - Benjamin T. Uveges; Kimberlee L. Sparks; Warren S. Ang; Hannah Monti; Fay-Wei Li; Jed P. Sparks (Isotopes in Environmental and Health Studies, 2026)

Bioaugmented graphene sand composite for manganese and pollutants removal in groundwater - Nur Raihan Ahmad Nahrawi; Wei Lun Ang; Ebrahim Mahmoudi; Ahmad Razi Othman; Abdul Wahab Mohammad (Groundwater for Sustainable Development, 2026)

Flash Joule carbothermal chemistry to synthesize porous silica-based ceramics for thermal safety - Feng Xu; Hongjian Zhang; Edison Huixiang Ang; Yisha Wang; Tianyang Cui; Yufei Lu; Zhentao Nie; Haoyang Wang; Wei Yang; Jixin Zhu (Chemical Engineering Journal, 2026)

An integrated meteorological adaptive simulation-optimization framework for real-time irrigation scheduling considering perfect weather forecasts - Kexin Li; Yanan Jiang; Ang Li; Xiangzhe Tian; Jiatong Lu; Tingting Wei; Jiangfeng Xiangli; Xifeng Huang; Yongmin Li; Shikun Sun (Agricultural Systems, 2026)

Unveiling switch coordinating wastewater anaerobic biological treatment: The role of quorum sensing and the potential thrust from signal molecule analogs - Chunyan Li; Wei Wei; Jia Meng; Ang Li (Water Research, 2026)

The CsWRKY3–CsHB7 transcriptional cascade promotes temperature-responsive peel pigmentation via CsCCD4b-mediated β-citraurin biosynthesis in citrus - Ranran Wei; Ang Fu; Yu Fang; Quan Sun; Zhijing Mo; Pengtao Yue; Ying Liang; Zongzhou Xie; Lijun Chai; Junli Ye; Xiuxin Deng (Molecular Plant, 2026)

Augmented soundscaping improves psychophysiological markers of mental fatigue and recovery - Syaheed B. Jabar; Kar Fye Alvin Lee; Elliot Chan; Jit Wei Aaron Ang; Bhan Lam; Vanessa Boey; Irene Lee; Woon-Seng Gan; Georgios Christopoulos (Building and Environment, 2026)

Molecular authentication of Gekko gecko using multienzyme isothermal rapid amplification technology - Jinjun Chai; Yating Zhang; Yuxin Xie; Ziqiang Xu; Ang Liu; Yi Yang; Lijun Gao; Wei Xia (Analytica Chimica Acta, 2026)

Carbon sequestration induced by enhanced silicate rock weathering in a temperate larch plantation in Northeastern China - Zhou Wu; Chenxia Su; Meixia Gao; Ronghua Kang; Daniel S. Goll; Meng Yao; Zihan Tai; Ang Wang; Qing-Wei Wang; Yunting Fang (Forest Ecology and Management, 2025)

Boosting the plateau capacity via phosphoric acid cross-linking strategy for phenolic resin-based hard carbon - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Haiyan Liu; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Biochar-mediated electron transfer in a spinel ferrite catalyst boosts peracetic acid activation for water decontamination - Lu Xia; Xinlan Li; Zhuojun Wei; Ang Liu; Jianqiu Chen; Jingge Shang (Chemical Engineering Journal, 2025)

Predicting urban residents' climate change risk perceptions: The role of heat and green space exposure indicators in Harbin's residential environment - Runsheng Jiang; Yu Dong; Lan Bai; Wei Dong; Ang Qu (Sustainable Cities and Society, 2025)

Assessing the human health risks from organophosphate esters: exposure assessment via wild freshwater fish consumption - Shuhui Wang; Ang Zhao; Bing Wang; Yifan Zhang; Qian Han; Emi Yang; Haode He; Chao Wei; Yuxia Yang; Jianzhong Xu; Mei Wang (Food Chemistry, 2025)

Sand encased by fine-grained sediment regulates methane migration through the gas hydrate stability zone - Jiliang Wang; Ang Li; Wei Zhang; Jin Sun; Jiecheng Zhang; Xueqing Zhou; Shiguo Wu (Earth and Planetary Science Letters, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

A critical review on graphitic carbon nitride-based electrodes in microbial fuel cells for bioelectricity generation and bioremediation - Ryan Yow Zhong Yeo; Wei Lun Ang; Wai Yin Wong; Eileen Hao Yu; Qi Hwa Ng; Soon Wah Goh; Mohd Nur Ikhmal Salehmin; Hassan Mohamed; Swee Su Lim (Journal of Environmental Chemical Engineering, 2025)

Water security through next-generation surface-engineered membrane technologies for heavy metal removal - Muhammad Syafiq Alias; Wei Lun Ang; Abdul Wahab Mohammad (Journal of Environmental Chemical Engineering, 2025)

Microplastic accumulation in four commercial fish from fish market: Implications for human dietary risk assessment - Renkang Jin; Li'ang Li; Shixiu Wang; Menghong Hu; Wei Huang; Youji Wang (Food Control, 2025)

Waterworks sludge coupled with biochar and pyrite as wetland substrates for enhanced nitrogen removal and greenhouse gases mitigation: First study on synergistic mechanisms - Yujie Yuan; Yaqian Zhao; Tao Zhang; Ting Wei; Yamei Cai; Lei Yang; Jingmiao Fu; Ang Liu; Anran Yang (Chemical Engineering Journal, 2025)

DiffRaman: A conditional latent denoising diffusion probabilistic model for enhancing bacterial identification via Raman spectra generation under limited data - Haiming Yao; Wei Luo; Ang Gao; Tao Zhou; Xue Wang (Analytica Chimica Acta, 2025)

Recent advances of constructed wetlands utilization under cold environment: Strategies and measures - Kaiyue Hao; Yaqian Zhao; Ting Wei; Du Wen; Ang Liu; Yulong Huang; Zhenzhen Chen (Process Safety and Environmental Protection, 2025)

Two new alkamides and a new polyacetylene glucoside from Achillea alpina L. - Ang Li; Xiu-Wei Li; Huan Guo; Qiang Guo; Xia Wu; Xiao-Qing Chen (Phytochemistry Letters, 2025)

Utilizing optical backscatter sensor and sediment traps for measuring sediment dynamics in low-energy marine environment - Chin Yik Lin; Su Shiung Lam; Jenn Wei Er; Wah Sze Lee; Jia Hui Ang (Marine Geology, 2025)

Relationship between LCZ and physical activity in residential areas: A mediating role of perceptions of heat risks in climate change - Wei Dong; Runsheng Jiang; Yu Dong; Ang Qu; Yuan Yuan (Urban Climate, 2025)

Utilization and perspectives of electricity generated from electro-wetland - Xiaorui Lei; Yaqian Zhao; Asheesh Kumar Yadav; Ang Liu; Yi Mao; Dan Wei; Fuhao Zhang; Xuechen Bai; Pratiksha Srivastava (Journal of Environmental Chemical Engineering, 2025)

High content of single-atomic sulfur in nano carbon spheres boosting potassium storage performance - Bin Cao; Zirong Guo; Huan Liu; Yu Ma; Wei Zhao; Yiheng Yang; Ang Li; Huaihe Song; Yaxiong Yang; Zhenglong Li; Wubin Du (Chemical Engineering Journal, 2025)

Unveiling the rise of microalgae-based foods in the global market: Perspective views and way forward - Wei Shan Ang; Phei Er Kee; John Chi-Wei Lan; Wei-Hsin Chen; Jo-Shu Chang; Kuan Shiong Khoo (Food Bioscience, 2025)

Peroxisomal biogenesis factor 11 as a novel target to trigger lipid biosynthesis and salt stress resistance in oleaginous Tetradesmus obliquus - Yunzhuan Xue; Wei Wang; Xiajule Sheng; Zexu Zheng; Zihan Wang; Fangling Ding; Jinjin Li; Zhiwei Sun; Yu’ang Cai; Xianhua Wang; Jiao Xue (Bioresource Technology, 2025)

Characterizing PPP ambiguity resolution residuals for precise orbit and clock corrections integrity monitoring - Mingqiang Xie; Ningbo Wang; Ahmed El-mowafy; Zishen Li; Ang Liu; Dongyan Wei (GPS Solutions, 2025)

Balls-on-ball structured S-scheme heterojunction with localized hotspot effects for boosted photothermal-assisted photocatalytic synthesis of hydrogen - Yu Shen; Jinqi Shi; Jieyu Lei; Pengnian Shan; Ang Bian; Wei Kong; Arkadii Proskurin; Mengtian Wu; Changyu Lu; Guangzhao Wang; Weilong Shi (Chemical Engineering Journal, 2025)

MXene-based mild photothermal therapy synergizes STING activation to enhance the efficacy of cancer vaccines post-cryoablation - Fuming Wang; Xiaodong Zhu; Qianwen Zhang; Minghui Xie; Lei He; Jiahao Guo; Ang Li; Qingsong Yang; Jijin Yang; Wei Li (Chemical Engineering Journal, 2025)

Analysis of the softening-melting mechanism of cold-bonded briquette from return sinter fines - Ying Li; Dejin Qiu; Manqing Li; Yuandong Xiong; Timo Fabritius; Su Cao; Ang Li; Abdallah Ahmed Elsherbiny; Jie Ren; Han Wei; Yaowei Yu (Journal of Cleaner Production, 2025)

Mechanistic insights into the hydrogel-supported catalyst for superior oxygen evolution performance - Yuxuan Wei; Lingling Xu; Kefan Shi; Hanwen Gong; Jiaming Hu; Xianghao Zhang; Meilan Pan; Edison Huixiang Ang (Chemical Engineering Journal, 2025)

VD/VDR-mediated ATG16L1 activation reduces Alzheimer’s disease-like pathology and cognitive decline - Zhixiong Huang; Wei Ang; Hefei Huang; Yanyan Wang (Molecular & Cellular Toxicology, 2025)

Effect of the LIF gene on the cell cycle and apoptosis of ovarian granulosa cells in white Muscovy ducks - Qing-hua Tao; Ning-ning Sun; Meng-shi Wang; Wan-xin Zhao; Wei Liu; Xu Zhang; Ang Li (Theriogenology, 2024)

Extreme heat event influences the toxic impacts of nano-TiO2 with different crystal structures in mussel Mytilus coruscus - Shuaishuai Wei; Yiran Mao; Inna M. Sokolova; Zhuoqing Li; Li'ang Li; Malik Shahzaib Khalid; Zhihan Tu; Zhen Zhong; Menghong Hu; Youji Wang (Science of The Total Environment, 2024)

Endophytic bacteria in Halogeton glomeratus from mining areas are mainly Sphingomonas pseudosanguinis, with a Cyanobacteria moving from roots to leaves to avoid heavy metals - Xisheng Tai; Ruiqi Yang; Jun Li; Ang Li; Wei Chen; Jiajia Ding (Rhizosphere, 2024)

Unique biogenesis and kinetics of hornwort Rubiscos revealed by synthetic biology systems - Zhen Guo Oh; Tanner Ashton Robison; Dan Hong Loh; Warren Shou Leong Ang; Jediael Zheng Ying Ng; Fay-Wei Li; Laura Helen Gunn (Molecular Plant, 2024)

Tire microplastic particles and warming inhibit physiological functions of the toxic microalga Alexandrium pacificum - Bole Wang; Dan Qiao; Bin Wen; Li'ang Li; Menghong Hu; Wei Huang; Youji Wang (Journal of Hazardous Materials, 2024)

Advanced membrane contactor coupled with electrodialysis metathesis for efficient carbon dioxide capture and waste salt remediation - Yundi Dong; Yangbo Qiu; Haili Wei; Chunhong Liu; Ke Wu; Junbin Liao; Edison Huixiang Ang; Jiangnan Shen (Desalination, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

A new strategy optimisation method for underwater flapping foil propulsion based on Twin-Delayed Deep Deterministic and Gaussian process regression - Yinghe Yang; Handi Wei; Dixia Fan; Ang Li (Ocean Engineering, 2024)

Synthesis of nitrogen-doped crystalline Ga2O3 thin films via trimethylgallium doped NH3/H2/N2/O2 premixed stagnation flames - Lun’ang Li; Shengfeng Luo; Mengzhao Chang; Guanjie Yin; Mingchen Sun; Jingrui Ma; Xiao Wei Sun; Igor Rahinov; Bo Zhou (Fuel, 2024)

Linkage engineered poly(heptazine imide) optimizes charge transfer for efficient photocatalytic H2O2 production: Regulating oxygen reduction pathway - Jianning Gao; Zhipeng Guo; Yihang Li; Bing Yang; Ang Wei (Chemical Engineering Journal, 2024)

Tris(1-chloro-2-propyl) phosphate enhances the adverse effects of biodegradable polylactic acid microplastics on the mussel Mytilus coruscus - Zhen Zhong; Wei Huang; Yiwei Yin; Shixiu Wang; Liming Chen; Zhaowen Chen; Jiacheng Wang; Li'ang Li; Mansoor Khalid; Menghong Hu; Youji Wang (Environmental Pollution, 2024)

Highly textured CMOS-compatible hexagonal boron nitride-based neuristor for reservoir computing - Haizhong Zhang; Jiayi Li; Xin Ju; Jie Jiang; Jing Wu; Dongzhi Chi; Diing Shenp Ang; Wei Hu; Rongshan Wei; Minmin Zhu; Xiaoqiang Lu (Chemical Engineering Journal, 2024)

Association Between Metal Exposure and Mitochondrial DNA Parameters and the Potential Mediation Effect of Oxidative Stress - Jing Xu; Meiduo Zhao; Xiaoyu Ge; Xiaolin Liu; Lanping Wei; Ang Li; Yayuan Mei; Guohuan Yin; Jingtao Wu; Qun Xu (Exposure and Health, 2024)

Analysis of resting status reveals distinct elevational variation in metabolisms of lizards - Zhong‐Wen Jiang; Liang Ma; Shi‐ang Tao; Cheng Wenda; Chuyu Cheng; Dan‐yang Wu; Wei‐Guo Du (Ecology, 2024)
Animals spend a considerable proportion of their life span at rest. However, resting status has often been overlooked when investigating how species respond to environmental conditions. This may induce a large bias in understanding the local adaptation of species across environmental gradients and their vulnerability to potential environmental change. Here, we conducted an empirical study on montane agamid lizards, combined with mechanistic modeling, to compare elevational variations in body temperature and metabolisms (cumulative digestion and maintenance cost) between resting and active status. Our study on three populations of an agamid lizard along an elevational gradient revealed a trend of decreasing body temperature toward higher elevations, the main contributor of which was resting status of the lizards. Using population‐specific reaction norms, we predicted greater elevational variation in hourly and cumulative digestion for resting lizards than for active lizards. Climate‐change impacts, estimated as the change in cumulative digestion, also show greater elevational variation when resting status is factored into the analysis. Further, our global analysis of 98 agamid species revealed that in about half of their combined distributional range, the contribution of resting status in determining the elevational variation in cumulative digestion and maintenance cost of lizards was greater than the contribution made by a lizard's active status. Our study highlights the importance of considering resting status when investigating how species respond to environmental conditions, especially for those distributed over tropical and subtropical mountain areas.

High-intensity exercise training in large yellow croaker is a compromise between disease resistance and fish welfare - Junjia Zeng; Ang Qu; Yacheng Deng; Pengxin Jiang; Ji Zhao; Jiaying Wang; Yue Liu; Wei Liu; Qiaozhen Ke; Fei Pu; Yaxian Li; Peng Xu (Aquaculture, 2024)

Physiological responses of the microalga Isochrysis galbana exposed to polystyrene microplastics with different particle sizes - Xue'en Jin; Yuyang Fang; Li'ang Li; Menghong Hu; James Kar-Hei Fang; Fahim Ullah Khan; Wei Huang; Youji Wang (Marine Environmental Research, 2024)

Sequential peroxi-coagulation-nanofiltration treatment of anaerobically treated palm oil mill effluent (POME) - Saiyidah Anisah Ismail; Siew Fen Chua; Wei Lun Ang; Ebrahim Mahmoudi; Abdul Wahab Mohammad; Wai Yin Wong (Journal of Water Process Engineering, 2024)

Source separation of urine and treatment: Impact on energy consumption, greenhouse gas emissions, and decentralised wastewater treatment process - Umakant Badeti; Jiaxi Jiang; Sanjay Kumarasingham; Abdulaziz Almuntashiri; Niren Kumar Pathak; Amit Chanan; Stefano Freguia; Wei Lun Ang; Noreddine Ghaffour; Ho Kyong Shon; Sherub Phuntsho (Desalination, 2024)

Dynamic Mechanical Response and Fracture Characteristics of Multi-flawed Rocks Exposed to Hydrostatic Confinements - Wei You; Feng Dai; Yi Liu; Ang Li (Rock Mechanics and Rock Engineering, 2024)

Aggregation-induced emission nanoparticles facilitating multicolor lateral flow immunoassay for rapid and simultaneous detection of aflatoxin B1 and zearalenone - Yi Zhang; Guoxin Chen; Xirui Chen; Xiaxia Wei; Xuan-ang Shen; Hu Jiang; Xiaoyang Li; Yonghua Xiong; Xiaolin Huang (Food Chemistry, 2024)

New formula of vegetation roughness height and Darcy–Weisbach friction factor in channel flow - Da-Qian Feng; Jing-Jing Fan; Wei-Jie Wang; Cheng-Xing Xia; Ang Li (Journal of Hydrology, 2024)

Advancements in polymeric membranes for challenging water filtration environments: A comprehensive review - Mei Qun Seah; Siew Fen Chua; Wei Lun Ang; Woei Jye Lau; Amir Mansourizadeh; Chidambaram Thamaraiselvan (Journal of Environmental Chemical Engineering, 2024)

Innovative sodium acrylate wastewater resource recovery through electrodialysis with integrated bipolar membranes - Hailong Cui; Huimin Ruan; Haili Wei; Edison Huixiang Ang; Yudi Dong; Hao Lu; Hongyu Liu; Junbin Liao; Yanqing Xu; Jiangnan Shen (Journal of Environmental Chemical Engineering, 2024)

Effect of poly(2-(dimethylamino)ethyl methacrylate) brush-grafted graphene oxide on polyamide layer formation and nanofiltration performance - Siew Fen Chua; Kar Mun Lam; Alireza Nouri; Ebrahim Mahmoudi; Wei Lun Ang; Woei Jye Lau; Abdul Wahab Mohammad (Journal of Environmental Chemical Engineering, 2024)

Nitrogen deposition mediates more stochastic processes in structuring plant community than soil microbial community in the Eurasian steppe - Wei Yang; Shuhan Zhang; Ang Li; Junjie Yang; Shuang Pang; Zonghao Hu; Zhiping Wang; Xingguo Han; Ximei Zhang (Science China Life Sciences, 2024)

Application of Artificial Neural Network to Evaluate Coalbed Methane Exploration Potential: A Case Study from Permian Longtan Formation, Shuicheng, Guizhou - Debashish Mondal; Sijie Han; Shuxun Sang; Xiaozhi Zhou; Fuping Zhao; Wei Gao; Peiming Zhou; Jinchao Zhang; Ang Xu (Natural Resources Research, 2024)

Assessment of the microbial electrochemical sensor (SENTRY™) as a potential wastewater quality monitoring tool for common pollutants found in Malaysia - Muhammad Farhan Hil Me; Wei Lun Ang; Ahmad Razi Othman; Abdul Wahab Mohammad; Ahmad Afiq Arshad Nasharuddin; Alijah Mohd Aris; Bee Chin Khor; Swee Su Lim (Environmental Monitoring and Assessment, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Corrigendum to “A comprehensive review on atmospheric water harvesting technologies: From thermodynamic concepts to mechanism and process development” - Hasan Nikkhah; Wan Mujiburahman Bin Wan Azmi; Ali Nikkhah; Amir Mohammad Najafi; Mohsen Mesbahi Babaei; Chua Siew Fen; Alireza Nouri; Abdul Wahab Mohammad; Ang Wei Lun; Ng Law Yong; Ebrahim Mahmoudi (Journal of Water Process Engineering, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Effects of elevated temperature and different crystal structures of TiO2 nanoparticles on the gut microbiota of mussel Mytilus coruscus - Zhuoqing Li; Li’ang Li; Inna Sokolova; Yueyong Shang; Wei Huang; Waiho Khor; James K.H. Fang; Youji Wang; Menghong Hu (Marine Pollution Bulletin, 2024)

Research on intelligent control theory and strategy of gas drainage pipe network based on graph theory - Aitao Zhou; Chang'ang Du; Kai Wang; Xihui Fan; Dongxu Wang; Wei Zhao; Han Gao (Fuel, 2024)

Particle-bound reactive oxygen species in cooking emissions: Aging effects and cytotoxicity - Lu Lu; Vanessa Y.Z. Ng; Melvyn Z.H. Tan; Nethmi Y. Kasthuriarachchi; Laura-Helena Rivellini; Yue Qian Tan; Lina Ang; Maximillian Viera; Boon Huat Bay; Wei Jie Seow; Alex K.Y. Lee (Atmospheric Environment, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Deep learning to obtain high-throughput morphological phenotypes and its genetic correlation with swimming performance in juvenile large yellow croaker - Junjia Zeng; Miaosheng Feng; Yacheng Deng; Pengxin Jiang; Yinlin Bai; Jiaying Wang; Ang Qu; Wei Liu; Zhou Jiang; Qian He; Zhijun Wang; Peng Xu (Aquaculture, 2024)

Insights into the fermentation potential of pollen: Manufacturing, composition, health benefits, and applications in food production - Yong Cheng; Beijun Ang; Chaoyi Xue; Zhenyu Wang; Liduan Yin; Tong Wang; Qiuming Chen; Zhaojun Wang; Maomao Zeng; Wei Zhang; Jie Chen; Zhiyong He (Trends in Food Science & Technology, 2024)

Corrigendum to “Nanofiltration membrane processes for water recycling, reuse and product recovery within various industries: A review” [JWPE, Vol. 45, (February 2022), 102478] - Nor Naimah Rosyadah Ahmad; Wei Lun Ang; Yeit Haan Teow; Abdul Wahab Mohammad; Nidal Hilal (Journal of Water Process Engineering, 2023)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

Target-oriented functionalization: Turning carbon nitride into a round-the-clock antimicrobial photocatalyst in water disinfection - Fengming Hou; Wei Wei; Yihang Li; Zhipeng Guo; Xiaoke Zhang; Jin Li; Ang Wei (Chemical Engineering Journal, 2023)

Effects of Environmental Heavy Metal Interactions on Renal Impairment: Epidemiological Evidence from Rural Northeastern China - Guohuan Yin; Xiaoyu Ge; Meiduo Zhao; Jing Xu; Ang Li; Yayuan Mei; Jingtao Wu; Xiaolin Liu; Lanping Wei; Qun Xu (Exposure and Health, 2023)

Exposure to cooking fumes is associated with perturbations in nasal microbiota composition: A pilot study - Xin Er Frances Jin; Dorrain Yanwen Low; Lina Ang; Lu Lu; Xin Yin; Yue Qian Tan; Alex King Yin Lee; Wei Jie Seow (Environmental Research, 2023)

Performance enhancement of proton exchange membrane fuel cells with bio-inspired gear-shaped flow channels - Yuzhi Ke; Baotong Zhang; Wei Yuan; Yafeng Bai; Yonghao Zhao; Zi'ang Liu; Zhenhe Lin; Xinze Li; Yangang Wang; Yong Tang (Chemical Engineering Journal, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Second-hand smoke and fine particulate matter exposures among multi-unit housing residents in Singapore: A pilot study - Lina Ang; Grace Tan; Yvette Van Der Eijk; Wei Jie Seow (Environmental Pollution, 2023)

Dietary exposure to nTiO2 reduces byssus performance of mussels under ocean warming - Saishuai Li; Hui Chen; Chunhua Liu; Inna M. Sokolova; Yuchuan Chen; Fujing Deng; Zhe Xie; Li'ang Li; Wei Liu; James Kar-Hei Fang; Daohui Lin; Menghong Hu; et al. (Science of The Total Environment, 2023)

A comprehensive review on atmospheric water harvesting technologies: From thermodynamic concepts to mechanism and process development - Hasan Nikkhah; Wan Mujiburahman Bin Wan Azmi; Ali Nikkhah; Amir Mohammad Najafi; Mohsen Mesbahi Babaei; Chua Siew Fen; Alireza Nouri; Abdul Wahab Mohammad; Ang Wei Lun; Ng law Yong; Ebrahim Mahmoudi (Journal of Water Process Engineering, 2023)

Modified-graphene quantum dot thin-film nanocomposite membrane for enhanced nanofiltration performance and antifouling properties: Minimal incorporation - Siew Fen Chua; Alireza Nouri; Ebrahim Mahmoudi; Wei Lun Ang; Abdul Wahab Mohammad (Journal of Water Process Engineering, 2023)

Management of tannery waste effluents towards the reclamation of clean water using an integrated membrane system: A state-of-the-art review - Ramesh Kumar; Aradhana Basu; Bhaskar Bishayee; Rishya Prava Chatterjee; Meeraambika Behera; Wei Lun Ang; Parimal Pal; Maulin Shah; Suraj K. Tripathy; Selvaraj Ambika; V. Aruna Janani; Sankha Chakrabortty; et al. (Environmental Research, 2023)

Atomic defects engineering on Fe-N4 sites for boosting oxygen reduction by in-situ ZnO thermal etching strategy - Shengjie Wei; Lei Li; Ang Li; Lei Zhang; Haibo Hu; Dawei Pang; Qinghua Zhang; Hai Xiao; Wenxing Chen (Chemical Engineering Journal, 2023)

Decoration of polylactic acid on graphene oxide for efficient adsorption of methylene blue and tetracycline - Alireza Nouri; Wei Lun Ang; Ebrahim Mahmoudi; Siew Fen Chua; Abdul Wahab Mohammad; Abdelbaki Benamor; Muneer M. Ba-Abbad; Choe Peng Leo (Chemosphere, 2023)

Distinct responses and range shifts of lizard populations across an elevational gradient under climate change - Zhong‐Wen Jiang; Liang Ma; Chun‐Rong Mi; Shi‐Ang Tao; Fengyi Guo; Wei‐Guo Du (Global Change Biology, 2023)
Ongoing climate change has profoundly affected global biodiversity, but its impacts on populations across elevations remain understudied. Using mechanistic niche models incorporating species traits, we predicted ecophysiological responses (activity times, oxygen consumption and evaporative water loss) for lizard populations at high‐elevation (

Differential physiological response of marine and freshwater microalgae to polystyrene microplastics - Hengtao Xu; Li’ang Li; Youji Wang; Kecheng Qiu; Siyang Chen; Jiangning Zeng; Ruijuan Liu; Qikun Yang; Wei Huang (Journal of Hazardous Materials, 2023)

Enhanced ultrasound-assisted pore-adjustable spherical imma-Fe3O4 catalytic-activated piezoelectric Fenton reaction for PDE-5i degradation - Zi-ang Jia; Qing-rui Zeng; Xun Zhang; Wei Feng (Journal of Environmental Chemical Engineering, 2023)

On the Key Dynamical Processes Supporting the 21.7 Zhengzhou Record-breaking Hourly Rainfall in China - Peng Wei; Xin Xu; Ming Xue; Chenyue Zhang; Yuan Wang; Kun Zhao; Ang Zhou; Shushi Zhang; Kefeng Zhu (Advances in Atmospheric Sciences, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Pollution profiles, influencing factors, and source apportionment of target and suspect organophosphate esters in ambient air: A case study in a typical city of Northern China - Ang Zhao; Chao Wei; Yue Xin; Xiaoli Wang; Qingqing Zhu; Jixing Xie; Haiyun Ma; Jianzhong Xu; Mei Wang (Journal of Hazardous Materials, 2023)

Intrinsic ionic confinement dynamic engineering of ionomers with low dielectric-k, high healing and stretchability for electronic device reconfiguration - Jingwen Wang; Yapeng Zheng; Wei Ren; Edison Huixiang Ang; Lei Song; Jixin Zhu; Yuan Hu (Chemical Engineering Journal, 2023)

Green development strategy of offshore wind farm in China guided by life cycle assessment - Jingjing Chen; Bingjing Mao; Yufeng Wu; Dongya Zhang; Yiqun Wei; Ang Yu; Lihong Peng (Resources, Conservation and Recycling, 2023)

Association of long-term air pollution exposure with the risk of prediabetes and diabetes: Systematic perspective from inflammatory mechanisms, glucose homeostasis pathway to preventive strategies - Yayuan Mei; Ang Li; Jiaxin Zhao; Quan Zhou; Meiduo Zhao; Jing Xu; Runkui Li; Yanbing Li; Kai Li; Xiaoyu Ge; Chen Guo; Yongjie Wei; et al. (Environmental Research, 2023)

The Combination of Platelet Rich Plasma Gel, Human Umbilical Mesenchymal Stem Cells and Nanohydroxyapatite/polyamide 66 Promotes Angiogenesis and Bone Regeneration in Large Bone Defect - Wei Liu; Yong Huang; Daqian Liu; Teng Zeng; Jingzhe Wang; Ang Li; Dawei Wang; Xiaoyu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Hsa_circ_0006732 regulates colorectal cancer cell proliferation, invasion and EMT by miR-127-5p/RAB3D axis - Tao Yang; Jufeng Sun; Wei Wang; Dongsheng Li; Xianxu Yang; Ang Jia; Yinda Ma; Zhongkai Fan (Molecular and Cellular Biochemistry, 2022)

How does the Nature of an Excipient and an Atheroma Influence Drug-Coated Balloon Therapy? - Karthic Anbalakan; Han Wei Toh; Hui Ying Ang; Martin Lindsay Buist; Hwa Liang Leo (Cardiovascular Engineering and Technology, 2022)

Sugar molasses as a sustainable precursor for the synthesis of graphene sand composite adsorbent for tetracycline and methylene blue removal - Alireza Nouri; Ebrahim Mahmoudi; Wei Lun Ang; Gasidit Panomsuwan; Oratai Jongprateep (Environmental Science and Pollution Research, 2022)

Genome-wide CRISPR activation screen identifies candidate receptors for SARS-CoV-2 entry - Shiyou Zhu; Ying Liu; Zhuo Zhou; Zhiying Zhang; Xia Xiao; Zhiheng Liu; Ang Chen; Xiaojing Dong; Feng Tian; Shihua Chen; Yiyuan Xu; Chunhui Wang; et al. (Science China Life Sciences, 2022)

Biodiversity and degradation potential of oil-degrading bacteria isolated from sediments of hydrothermal and non-hydrothermal areas of the Southwest Mid-Indian Ocean Ridge - Haolei Shi; Jiangfeng Cheng; Wei Gao; Meng Ma; Ang Liu; Tianyi Hu; Bin Han; Li Zheng (Environmental Science and Pollution Research, 2022)

Deduction and exploration of the evolution and function of vertebrate GFPT family - Si-ang Wei; Ran Xu; Yu-yao Ji; Zhi-wen Ding; Yun-zeng Zou (Genes & Genomics, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Carbon limitation overrides acidification in mediating soil microbial activity to nitrogen enrichment in a temperate grassland - Qiushi Ning; Stephan Hättenschwiler; Xiaotao Lü; Paul Kardol; Yunhai Zhang; Cunzheng Wei; Chengyuan Xu; Jianhui Huang; Ang Li; Junjie Yang; Jing Wang; Yang Peng; et al. (Global Change Biology, 2021)
Higher ecosystem nitrogen (N) inputs resulting from human activities often suppress soil microbial biomass and respiration, thereby altering biogeochemical cycling. Soil acidification and carbon (C) limitation may drive these microbial responses, yet their relative importance remains elusive, which limits our understanding of the longer term effects of increasing N inputs. In a field experiment with continuous N addition at seven different rates from 0 to 50 g N m −2 year −1 over 6 years in a temperate grassland of Inner Mongolia, China, we examined the responses of soil microbial biomass and respiration to changes in soil acidity and C availability by adding lime and/or glucose to soil samples. Soil microbial biomass and respiration did only weakly respond to increasing soil pH, but increased strongly in response to higher C availability with increasing N addition rates. Soil net N immobilization increased in response to glucose addition, and soil microbial biomass increased at higher rates than microbial respiration along the gradient of previous N addition rates, both suggesting increasingly reinforced microbial C limitation with increasing N addition. Our results provide clear evidence for strong N‐induced microbial C limitation, but only little support for soil acidity effects within the initial pH range of 4.73–7.86 covered by our study. Field data support this conclusion by showing reduced plant C allocation belowground in response to N addition, resulting in soil microbial C starvation over the long term. In conclusion, soil microbial biomass and respiration under N addition were strongly dependent on C availability, most likely originating from plant belowground C inputs, and was much less affected by changes in soil pH. Our data help clarify a long‐standing debate about how increasing N input rates affect soil microbial biomass and respiration, and improve the mechanistic understanding of the linkages between ecosystem N enrichment and C cycling.

Influences of Loading Method and Notch Type on Rock Fracture Toughness Measurements: From the Perspectives of T-Stress and Fracture Process Zone - Mingdong Wei; Feng Dai; Yi Liu; Ang Li; Zelin Yan (Rock Mechanics and Rock Engineering, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Dynamic Compression–Shear Response and Failure Criterion of Rocks with Hydrostatic Confining Pressure: An Experimental Investigation - Hongbo Du; Feng Dai; Mingdong Wei; Ang Li; Zelin Yan (Rock Mechanics and Rock Engineering, 2021)

Data Analysis and Key Parameters of Typical Water Hazard Control Engineering in Coal Mines of China - Lin Mou; Shuning Dong; Wanfang Zhou; Wei Wang; Ang Li; Zhiyuan Shi (Mine Water and the Environment, 2020)

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury - Zhijian Wei; Baoyou Fan; Han Ding; Yang Liu; Haoshuai Tang; Dayu Pan; Jiaxiao Shi; Pengyuan Zheng; Hongyu Shi; Heng Wu; Ang Li; Shiqing Feng (Molecular and Cellular Biochemistry, 2019)

Exploring Local Perceptions of and Attitudes toward Endangered François’ Langurs (Trachypithecus francoisi) in a Human-Modified Habitat - Kefeng Niu; Wei Liu; Zhi Xiao; Ankang Wu; Tianyou Yang; Isidoro Riondato; Amanda L. Ellwanger; Andie Ang; Marco Gamba; Yeqin Yang; Cristina Giacoma (International Journal of Primatology, 2019)

Al(III)-binding properties at the molecular level of soil DOM subjected to long-term manuring - Jianchao Zhang; Ang Hu; Boren Wang; Wei Ran (Journal of Soils and Sediments, 2019)

Erratum to: Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Conditioning of Synthetic Sludge and Anaerobically Digested Sludge Using Chitosan, Organic Polyelectrolytes and Inorganic Metal Cations to Enhance Sludge Dewaterability - Shiew Wei Lau; Tushar Kanti Sen; Han Bing Chua; Ha Ming Ang (Water, Air, & Soil Pollution, 2017)

Anti-Collision Assessment and Prediction Considering Material Corrosion on an Offshore Protective Device - Ang Qiu; Xiangxi Han; Hongyu Qin; Wei Lin; Youhong Tang (Journal of Marine Science and Engineering, 2017)
Corrosion deterioration of steel can heavily degrade the performance of marine and offshore structures. A typical steel protective device, which has worked for a dozen years in a river estuary, is selected as the research object. Its current corrosion response is measured on site and its further corrosive response is predicted based on measurement data and the structure’s current state. Nonlinear finite element method is utilized to analyze the degradation of the protective device’s anti-collision performance. Meanwhile the rubber buffer effect has been investigated for its anti-collision on the protective device. A prediction method is proposed that can accurately forecast degradation of the anti-collision performance of a protective device as time progresses.

Physiological and transcriptional analysis reveals pathways involved in iron deficiency chlorosis in fragrant citrus - Long-Fei Jin; Yong-Zhong Liu; Wei Du; Li-Na Fu; Syed Bilal Hussain; Shu-Ang Peng (Tree Genetics & Genomes, 2017)

Long-term variation in the salinity of the Southern Yellow Sea Cold Water Mass, 1976–2006 - Ang Li; Fei Yu; Guangcheng Si; Chuanjie Wei (Journal of Oceanography, 2017)

Antituberculosis agents bearing the 1,2-disubstituted benzimidazole scaffold - Keng Yoon Yeong; Chee Wei Ang; Mohamed Ashraf Ali; Hasnah Osman; Soo Choon Tan (Medicinal Chemistry Research, 2017)

Nitrogen removal and microbial community shift in an aerobic denitrification reactor bioaugmented with a Pseudomonas strain for coal-based ethylene glycol industry wastewater treatment - Cong Du; Chong-Wei Cui; Shan Qiu; Sheng-Nan Shi; Ang Li; Fang Ma (Environmental Science and Pollution Research, 2017)

Role of the Helix in Talin F3 Domain (F3 Helix) in Talin-Mediated Integrin Activation - Ang Li; Qiang Guo; Ailin Wei; Yaliang Zhou; Weiming Hu (Cell Biochemistry and Biophysics, 2017)

Adsorption behavior of tetracycline by extracellular polymeric substrates extracted from Klebsiella sp. J1 - Ang Li; Shanshan Pi; Wei Wei; Ting Chen; Jixian Yang; Fang Ma (Environmental Science and Pollution Research, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Environmental and cortisol-mediated control of Ca2+ uptake in tilapia (Oreochromis mossambicus) - Chia-Hao Lin; Wei-Chun Kuan; Bo-Kai Liao; Ang-Ni Deng; Deng-Yu Tseng; Pung-Pung Hwang (Journal of Comparative Physiology B, 2016)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

Antimycobacterial activity and in silico study of highly functionalised dispiropyrrolidines - Ang Chee Wei; Mohamed Ashraf Ali; Yeong Keng Yoon; Sy Bing Choi; Hasnah Osman; Vijay H. Masand; Tan Soo Choon (Medicinal Chemistry Research, 2015)

Overexpression of CsCLCc, a Chloride Channel Gene from Poncirus trifoliata, Enhances Salt Tolerance in Arabidopsis - Qingjiang Wei; Yongzhong Liu; Gaofeng Zhou; Qiaohong Li; Chengquan Yang; Shu-ang Peng (Plant Molecular Biology Reporter, 2013)

Combined structure-based pharmacophore, virtual screening, and 3D-QSAR studies of structural diverse dehydrosqualene synthase inhibitors - Fei Peng; Aihua Peng; Youfu Luo; Wei Huang; Bo Han; Xiaoyan Yang; Wei Ang; Tao Yang; Mingli Xiang; Cheng Peng; Gu He (Medicinal Chemistry Research, 2013)

Isolation and characterization of polymorphic microsatellite markers in the fish Garra orientalis (oriental sucking barb) - Li-Wei Su; Zhi-Zhi Liu; Cong-Tao Wang; Zhen Zeng; Ang-Yu Liu; Wen-Qiao Tang; Jin-Quan Yang (Conservation Genetics Resources, 2013)

Tree‐ring‐based temperature reconstruction for the northern Greater Higgnan Mountains, China, since A.D. 1717 - Tongwen Zhang; Yujiang Yuan; Wenshou Wei; Shulong Yu; Ruibo Zhang; Huaming Shang; Feng Chen; Zi'ang Fan; Li Qin (International Journal of Climatology, 2013)
In this paper, ring‐width chronologies of pine trees ( Pinus sylvestris var. mongolica ) from one sampling site in the northern Greater Higgnan Mountains, China, were constructed. The results of growth‐climate responses show that mean temperature is the limiting factor affecting radial growth of pine trees in the study area. Consequently, mean temperature from May to October from 1717 to 2008 has been reconstructed using the standard chronology. For the calibrated period (1957‐2008), the explained variance of the reconstruction is 57%. The characteristics of the reconstruction expose that mean temperature has increased since the 1970s, and the decade 2000s and 1990s are also ranked as the warm decades on record. However, this period from 1970s to now is not exceptional within the past 300 years. By applying an 11‐year moving average to the reconstruction, three warm periods and three cold periods are evident. The warm and cold periods of the reconstructed mean temperature correspond well with other reconstructions. Power spectral and wavelet analysis demonstrated the existence of significant ∼70‐ and ∼100‐year cycles of variability. Furthermore, the reconstruction and North Atlantic Oscillation Index showed a significant positive correlation ( r = 0.34, n = 136, p

QSAR classification of metabolic activation of chemicals into covalently reactive species - Chin Yee Liew; Chuen Pan; Andre Tan; Ke Xin Magneline Ang; Chun Wei Yap (Molecular Diversity, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Maximum Grade Approach to Surplus Floodwater of Hyperconcentration Rivers in Flood Season and its Application - Xun-Gui Li; Xia Wei; Nai-Ang Wang; Hong-Yi Cheng (Water Resources Management, 2011)